The dyslexia-associated protein KIAA0319 interacts with adaptor protein 2 and follows the classical clathrin-mediated endocytosis pathway. - Levecque, C; Velayos-Baeza, A; Holloway, Z; Monaco, A (2009)
Recently, genetic studies have implicated KIAA0319 in developmental dyslexia, the most common of the childhood learning disorders. The first functional data indicated that the KIAA0319 protein is expressed on the plasma membrane and may be involved in neuronal migration. Further analysis of the subcellular distribution of the overexpressed protein in mammalian cells indicates that KIAA0319 can colocalize with the early endosomal marker early endosome antigen 1 (EEA1) in large intracellular vesicles, suggesting that it is endocytosed. Antibody internalization assays with full-length KIAA0319 and deletion constructs confirmed that KIAA0319 is internalized and showed the importance of the cytoplasmic juxtamembranal region in this process. The present study has identified the medium subunit (mu2) of adaptor protein 2 (AP-2) as a binding partner of KIAA0319 in a yeast two-hybrid screen. Using Rab5 mutants or depletion of the mu-subunit of AP-2 or clathrin heavy chain by RNA interference, we demonstrate that KIAA0319 follows a clathrin-mediated endocytic pathway. We also identify tyrosine-995 of KIAA0319 as a critical amino acid required for the interaction with AP-2 and subsequent internalization. These results suggest the surface expression of KIAA0319 is regulated by endocytosis, supporting the idea that the internalization and recycling of the protein may be involved in fine tuning its role in neuronal migration.